Penerapan Asas Mempersulit Proses Perceraian Pada Persidangan di Pengadilan Agama Bengkulu - Slamet Muljono; Edytiawarman Edytiawarman; Dimas Dwi Arso; Nurhani Fithriah (Wajah Hukum, 2021)
Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. But in reality, there are still many households that end up in divorce. To prevent divorce in the household, positive marriage law in Indonesia adheres to the principle of complicating divorce, the application of which is manifested in the necessity for reasons as regulated in law and divorce can only be made with a decision to file will be implemented at the time of the divorce process in court Religion. This research aims to understand the application of the principle of complicating divorce in the Bengkulu Class 1A Religious Court, with the following problems: What are the factors causing the divorce in the Bengkulu Class 1A Religious Court and, how does the implementation of the principle complicate the divorce process in the divorce trial at the Bengkulu Religious Court. For the purposes of this study, empirical research methods are used, which directly search for data in the field. In analyzing the field data, sociological analysis and normative analysis were used to obtain comprehensive analysis results. Based on the results of field research, it was concluded that divorce in Bengkulu was generally based on economic reasons, and consecutively due to domestic violence, and reasons for having an affair. Of the reasons put forward by the parties who filed for or sue for divorce, most of them are due to economic reasons.